Comparison Between Intraperitoneal and Intravenous Lidocaine for Postoperative Analgesia After Elective Abdominal Hysterectomy, a Double-Blind Placebo Controlled Study - Saghar Samimi; Arman Taheri; Fatemeh Davari Tanha (Tehran University of Medical Sciences, 2016)
Objective: To compare the efficacy of intravenous and intraperitoneal injection of lidocaine and normal saline in relieving postoperative pain after elective abdominal hysterectomy. Materials and methods: For this double-blind randomized controlled study 109 patients undergoing elective abdominal hysterectomy were randomly allocated to three groups :1) IV group (intravenous injection group) received intravenous lidocaine %2 bolus 1.5mg/kg 30 min before incision and then a continuous lidocaine infusion of 2mg/kg and before the wound closure an intraperitoneal injection of N/S , 2) IP group (intraperitoneal group) received intravenous N/S and intraperitoneal lidocaine 3mg/kg , 3) P group (placebo, N/S) received both intravenous and intraperitoneal N/S. The pain scores (VAS) at rest, total morphine consumption , the time to first need for rescue analgesic ,incidence of lidocaine related adverse effects and nausea and vomiting were recorded at 0,2,4,8,12 and 24 hrs postoperatively. Results: The VAS scores were significantly lower in IP and IV groups compared with placebo (p = 0.001). Total consumption of morphine (p = 0.001) and time to firs request of recue analgesic (p = 0.001) were lower too in IP and IV groups.Incidence of vomiting was comparable between groups (p < 0.05) but nausea was higher in control group (p > 0.05).There were not notable lidocaine-related adverse effects. IP and IV groups were not statistically different for all investigated variables. Conclusion: This study showed lidocaine administration both intravenously and intraperitoneally are effective in reducing the postoperative pain and also have opioid sparing effect and can be safely used in elective abdominal hysterectomy without any major adverse effects.